Changes in the activity levels and financing sources of Israel's private for-profit hospitals in the wake of reforms to the public-private divide - Royi Barnea; Adi Niv-Yagoda; Yossi Weiss (BMC, 2021)
Abstract Background The Israeli National Health Insurance Law provides permanent residents with a basket of healthcare services through non-profit public health insurance plans, independently of the individual's ability to pay. Since 2015, several reforms and programs have been initiated that were aimed at reinforcing public healthcare and redressing negative aspects of the health system, and specifically the constant rise in private health expenditure. These include the "From Reimbursement-to-Networks Arrangement", the "Cooling-off Period" program and the program to shorten waiting times. The objectives of this study were to identify, describe, and analyze changes in private hospitals in 1) the volume of publicly and privately funded elective surgical procedures; and 2) private health expenditure on surgical procedures. Methods Data on the volume and funding of surgical procedures during 2013-2018 were obtained from Assuta Medical Center, Hertzelia Medical Center, the Israeli Ministry of Health and the Central Bureau of Statistics. The changes in the volume and financing sources of surgical activities in private hospitals, in the wake of the reforms were analyzed using aggregate descriptive statistics. Results Between 2013 and 2018 the volume of surgical activities in private for-profit hospitals increased by 7%. Between 2013 and 2017, the distribution of financing sources of surgical procedures in private hospitals remained stable, with most surgical procedures (75-77%) financed by the voluntary health insurance programs of the health plans (HP-VHI). In 2018, following the regulatory reforms, a significant change in the distribution of financing sources was observed: there was a sharp decline in the volume of HP-VHI-funded surgical procedures to 26%. Concurrently, the share of publicly-funded surgical procedures performed in private hospitals increased to 56% in 2018.,. During the study period, private spending on elective surgical procedures in private hospitals declined by 53% while public funding for them increased by 51%. Conclusions and policy implications In the wake of the reforms, there was a substantial shift from private to public financing of elective surgical activity in private hospitals. Private for-profit hospitals have become important providers of publicly-funded procedures. It is likely that the reforms affected the public-private mix in the financing of elective surgical procedures in those hospitals, but due to the absence of a control group, causality cannot be proven. It is also unclear whether waiting times were shortened. Health reforms must be accompanied by a clear and comprehensive set of indicators for measuring their success.